Cellular and molecular mechanism for secretory autophagy - Kimura, Tomonori (Autophagy, 2017)
Macroautophagy/autophagy plays a role in unconventional secretion of leaderless cytosolic proteins. Whether and how secretory autophagy diverges from conventional degradative autophagy is unclear. We have shown that the prototypical secretory autophagy cargo IL1B/IL-1β (interleukin 1 β) is recognized by TRIM16, and that this first to be identified secretory autophagy receptor interacts with the R-SNARE SEC22B to jointly deliver cargo to the MAP1LC3B-II-positive sequestration membranes. Cargo secretion is unaffected by knockdowns of STX17, a SNARE catalyzing autophagosome-lysosome fusion as a prelude to cargo degradation. Instead, SEC22B in combination with plasma membrane syntaxins completes cargo secretion. Thus, secretory autophagy diverges from degradative autophagy by using specialized receptors and a dedicated SNARE machinery to bypass fusion with lysosomes.